Interventions to promote medication adherence for chronic diseases in India: a systematic review - Tolley, Abraham; Hassan, Refaat; Sanghera, Rohan; Grewal, Kirpal; Kong, Ruige; Sodhi, Baani; Basu, Saurav (Frontiers in Public Health, 2023)
Introduction: Cost-effective interventions that improve medication adherence are urgently needed to address the epidemic of non-communicable diseases (NCDs) in India. However, in low- and middle-income countries like India, there is a lack of analysis evaluating the effectiveness of adherence improving strategies. We conducted the first systematic review evaluating interventions aimed at improving medication adherence for chronic diseases in India. Methods: A systematic search on MEDLINE, Web of Science, Scopus, and Google Scholar was conducted. Based on a PRISMA-compliant, pre-defined methodology, randomised control trials were included which: involved subjects with NCDs; were located in India; used any intervention with the aim of improving medication adherence; and measured adherence as a primary or secondary outcome. Results: The search strategy yielded 1,552 unique articles of which 22 met inclusion criteria. Interventions assessed by these studies included education-based interventions (n=12), combinations of education-based interventions with regular follow up (n=4), and technology-based interventions (n=2). Non-communicable diseases evaluated commonly were respiratory disease (n=3), type 2 diabetes (n=6), cardiovascular disease (n=8) and depression (n=2). Conclusions: Although the vast majority of primary studies supporting the conclusions were of mixed methodological quality, patient education by CHWs and pharmacists represent promising interventions to improve medication adherence, with further benefits from regular follow-up. There is need for systematic evaluation of these interventions with high quality RCTs and their implementation as part of wider health policy.